Zero-Dose Childhood Vaccination Status in Rural Democratic Republic of Congo: Quantifying the Relative Impact of Geographic Accessibility and Attitudes toward Vaccination - Branly Kilola Mbunga; Patrick Y. Liu; Freddy Bangelesa; Eric Mafuta; Nkamba Mukadi Dalau; Landry Egbende; Nicole A. Hoff; Jean Bosco Kasonga; Aimée Lulebo; Deogratias Manirakiza; Adèle Mudipanu; Nono Mvuama; et al. (Vaccines, 2024)
Despite efforts to increase childhood vaccination coverage in the Democratic Republic of the Congo (DRC), approximately 20% of infants have not started their routine immunization schedule (zero-dose). The present study aims to evaluate the relative influence of geospatial access to health facilities and caregiver perceptions of vaccines on the vaccination status of children in rural DRC. Pooled data from two consecutive nationwide immunization surveys conducted in 2022 and 2023 were used. Geographic accessibility was assessed based on travel time from households to their nearest health facility using the AccessMod 5 model. Caregiver attitudes to vaccination were assessed using the survey question “How good do you think vaccines are for your child?” We used logistic regression to assess the relationship between geographic accessibility, caregiver attitudes toward vaccination, and their child’s vaccination status. Geographic accessibility to health facilities was high in rural DRC, with 88% of the population living within an hour’s walk to a health facility. Responding that vaccines are “Bad, Very Bad, or Don’t Know” relative to “Very Good” for children was associated with a many-fold increased odds of a zero-dose status (ORs 69.3 [95%CI: 63.4–75.8]) compared to the odds for those living 60+ min from a health facility, relative to <5 min (1.3 [95%CI: 1.1–1.4]). Similar proportions of the population fell into these two at-risk categories. We did not find evidence of an interaction between caregiver attitude toward vaccination and travel time to care. While geographic access to health facilities is crucial, caregiver demand appears to be a more important driver in improving vaccination rates in rural DRC.